(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
This paper study about basic concept of financial inclusion and its role in providing services to the weaker section of society at reasonable prices with digital mode. Here the study comprises how the digital era seems to one of lower cost prospect which helps in balancing economic and financial aspects, improving employment opportunities further adds national income and economic development of a nation. This paper shows highlights of the vision initiated by Government of India as a provision focuses upon digital empowerment & good governance and the initiatives taken under digital technology in order to spread awareness and its usage among the masses . This paper is descriptive in nature.